Association of Serum Total Osteocalcin Concentrations With Endogenous Glucocorticoids and Insulin Sensitivity Markers in 12-Year-Old Children: A Cross-Sectional Study - Seppä, Satu; Tenhola, Sirpa; Voutilainen, Raimo (Frontiers in Endocrinology, 2019)
Background: Osteocalcin (OC) is an osteoblast-derived marker of bone turnover that has recently been linked to glucose metabolism, glucocorticoid action and cardiovascular risk. Objective: We determined whether serum total OC (tOC) is associated with cardiometabolic factors, such as insulin sensitivity (IS) markers and endogenous glucocorticoids in 12-year-old children. In addition, we assessed whether low birth weight or exposure to maternal preeclampsia affect tOC concentrations. Methods: In this cross-sectional study, 192 children (109 girls) were studied at 12 years of age. Seventy of them had been born small (SGA), 78 appropriate for gestational age (AGA), and 44 from preeclamptic pregnancies (PRE) as AGA. Blood pressure was measured, and fasting blood samples were collected for markers of glucose metabolism, osteoblast, adipocyte and adrenocortical function. IS was estimated by Quantitative Insulin Sensitivity Check Index (QUICKI). Free cortisol index (FCI) was calculated as serum cortisol/corticosteroid binding globulin. Results: The highest tOC concentrations were detected in midpubertal children (Tanner B/G stage 3). The children in the highest tOC quartile (n=48) had lower body mass index (BMI), waist-to-height ratio, diastolic blood pressure, leptin, cortisol/cortisone ratio and FCI, and higher insulin-like growth factor I (IGF-I), IGF-binding protein-1 (IGFBP-1), IGFBP-3 and alkaline phosphatase (ALP) than those in the lower tOC quartiles (p<0.02 for all). QUICKI was similar in these subgroups. In logistic regression analysis, pubertal developmental stages 2 and 3, high ALP, IGF-I, and low FCI and BMI (p<0.02 for all) were associated independently with higher tOC. The means of serum tOC and IS markers were similar in the SGA, AGA and PRE subgroups. Conclusions: In both sexes, the highest tOC levels were detected in midpubertal children reflecting the fast pubertal growth phase. Higher tOC levels were associated with lower BMI and FCI, whereas no association was found with IS. Birth weight or exposure to preeclampsia had no effect on tOC concentrations.